The influence of sex on sleep characteristics in the adult and older adult population: findings from the EPISONO sleep study - Silva, Mayra dos Santos; Tempaku, Priscila Farias; Andersen, Monica Levy; Tufik, Sergio; Poyares, Dalva (Frontiers in Sleep, 2025)
IntroductionSleep is a restorative behavior and is critical for overall health, but differences in sleep patterns between men and women can be seen over the years.AimTo prospectively analyze the polysomnographic findings of adults and older adults who participated in two editions of EPISONO, according to sex.MethodsThe population-based prospective longitudinal study included 688 individuals. Of these, there were 389 women and 299 men. All examinations and tests were undertaken using the same protocols at both times, at baseline and 8 years later. All participants completed an institutional questionnaire and a range of other questionnaires on health and sleep parameters. They also underwent full-night polysomnography (PSG) and peripheral blood collection for biochemical and hematological measurements. In both editions (2007 and 2015), physical and anthropometric assessments were also assessed. Exclusion criteria: pregnant or lactating women, individuals with self-care limitations (physical or mental), and night-shift workers.ResultsWe observed that adult women showed a greater REM latency, adult and older adult women spent more time in N3 than men, and an increased periodic leg movement index in older adult women. Men (adults and older adults) remained longer in N1, had a higher number of awakenings, and of apnea-hypopnea index. Age was shown to be an influencing factor for changes in arousal index and apnea-hypopnea index. This study prospectively evaluated, with full-night PSG, the sleep of the general population and reported significant findings according to sex and age, suggesting that some sleep parameters change differently in men and women, as we age.